The urban poor: profile and constraints affecting their participation in allotment gardens - HOUESSOU, Mawuna Donald; SONNEVELD, Ben G. J. S.; AOUDJI, KOSSI NOUNAGNON AUGUSTIN; Snelder, Denyse J. R. M.; ADEGBIDI, ANSELME BIENVENU E. ADÉNIYI; De Cock Buning, Tjard (My University, 2023)
Rapid global urbanisation has seen a growing number of urban poor who lack natural endowments to cope with food shortages. Broadening their safety nets merits urgent political attention but requires understanding their profiles. A survey among 88 urban poor in Benin found that they had low educational and income levels, overcrowded and unsanitary housing conditions, and limited access to social services and health facilities; 76 per cent of them were food insecure, influenced by city, gender, ownership of a motorbike, and access to health facilities. Engaging them in allotment gardens requires farming skills, financial capital, and safety issues.
Keywords: Urbanization; poverty; foodsecurity; urban planning; urban agriculture; cities; Benin